Determination of optimum tilt and azimuth angle of BiSPVT system along with its performance due to shadow of adjacent buildings. (February 2021) - Yadav, Somil; Hachem-Vermette, Caroline; Panda, Sarat Kumar; Tiwari, G.N.; Mohapatra, Smruti Sourava
Highlights: Evaluation of insolation when BIPV panel is subjected to shadow due to adjacent buildings. Optimum azimuth and tilt angle of BIPV panel for harnessing maximum insolation. Optimum azimuth angle changes with change in plan orientation of adjacent building. Efficiency of the BIPV panel increases when water is assumed to be flown over it. Abstract: Development of a BIPV system with appropriate azimuth and tilt angle on top of a suitable existing or new building in urban areas is a possible option to generate both electrical and thermal energies and also to create an additional living space. These azimuth and tilt angles are significantly influenced by the shadow of the neighborhood's buildings. The relative height, plan orientation, plan area, position, and horizontal distance of the neighborhood's buildings are critical parameters for determining optimum azimuth and tilt angle to receive maximum insolation. Present proposed model accurately calculates these angels and the energy, and the model also works well when water flows over the BIPV panel from an overhead tank through gravity with an aim to increase the efficiency of PV panel. The periodic nature of relevant parameters is considered in the thermal modeling of the BiSPVT system. Results indicate that the optimum azimuth angle from south-facing increases with a rise in the latitude angle of the place. The optimum tilt angle depends on the corresponding latitude and the different contributing parts of total insolation. The electrical output of a south-facing BiSPVT system with a tilt angle equal to latitude is increased by 3.7% when BiSPVT system is installed at optimum azimuth and tilt angle. The output is further enhanced by 4.3% when water is flown at the rate of 1.1 kgs −1 over the PV panel.